Exploring the nexus of leadership style, purchasing efficiency, and sustainable economic performance: fiscal term as moderator - Benny Hutahayan; Firera Firera; Mochammad Al Musadieq; Solimun Solimun (Cogent Business & Management)
This research examines the dynamics between leadership style, procurement efficiency, and sustainable economic performance, with a focus on the moderating role of fiscal terms within Indonesia’s upstream oil and gas industry. The study uses pooled data—comprising both time series and cross-sectional data—collected over four years (2018–2021) from 20 Production Sharing Contract Contractors (PSCCs) during the preliminary Plan of Development (POD) phase, along with survey responses from 80 participants. By employing Structural Equation Modeling (SEM) via WarpPLS, the analysis reveals a significant impact of leadership style on procurement efficiency, which subsequently influences sustainable economic performance. Additionally, the study finds that fiscal terms significantly moderate the relationship between procurement efficiency and sustainable economic performance. This research introduces a novel and comprehensive framework that illustrates the effect of leadership style on sustainable economic performance—mediated by procurement efficiency and further moderated by fiscal terms—thus contributing to existing literature and providing strategic insights for practitioners in the upstream oil and gas sector.